The Role of Nurse Service Quality and Emotional Care in Improving Patient Trust and Recovery Outcomes in Bandung Healthcare Facilities - Hudzaifah Al Fatih; Tita Puspita Ningrum (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study examined the role of nurse service quality and emotional care in improving patient trust and recovery outcomes in healthcare facilities in Bandung. A quantitative, cross-sectional design was used, involving patients who had received nursing services. Data were collected through structured questionnaires and analyzed using descriptive and inferential statistical methods. The findings showed that nurse service quality and emotional care had significant positive effects on patient trust. Patient trust also significantly influenced recovery outcomes and served as a mediating variable between service quality and emotional care. Service quality demonstrated a stronger effect on trust, while emotional care played an important role in strengthening the nurse–patient relationship. The results indicated that recovery outcomes were influenced not only by technical aspects of care but also by emotional and relational factors. This study concluded that integrating service quality and emotional care through a trust-based approach could more effectively enhance patient recovery and support the development of patient-centered healthcare services.